Bioprocess and bioproducts : technology trends and opportunities - Indo-US Conference on "Bioprocess and Bioproducts: Technology Trends and Opportunities" (2008 : Hyderabad, India); Biswas, Soumitra; Kaushik, Nirmala; Pandey, Ashok; India. Dept. of Science and Technology; Indo-US Science & Technology Forum; Technology Information, Forecasting, and Assessment Council (India) (New Delhi : Asiatech Publishers, 2009)
Contributed seminar papers presented at an Indo-US Conference on "Bioprocess and Bioproducts: Technology Trends and Opportunities" held at Hyderabad during Nov. 27-28, 2008 organized by TIFAC, Dept. of Science & Tech, Govt. of India in collaboration with Indo-US Science and Technology Forum.
Fakulti Agro-Industri dan Sumber Asli
Includes bibliographical references and index.
Keywords: Biochemical engineering -- Congresses; Biochemical engineering -- India -- Congresses; Biological products -- India -- Congresses